Supercapacitor based on mixed MOFs electrode film and preparation method thereof

By using MOFs materials mixed with Ni3 (HITP)2 and Cu2 (OHPTP) in supercapacitors and the adapted ionic liquid electrolyte, the problem of insufficient capacitance performance and charging speed of conductive MOFs-based supercapacitors is solved, and a significant performance improvement is achieved.

CN119601385AActive Publication Date: 2025-03-11HUAZHONG UNIV OF SCI & TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411726397.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-11
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Conductive MOFs-based supercapacitors have problems with low capacitance performance and slow charging speed.

Method used

A multi-porous electrode film consisting of Ni3 (HITP)2 and Cu2 (OHPTP) is used to mix two MOFs materials with different pore sizes, a multi-porous electrode film composed of a binder, and an ionic liquid electrolyte that is suitable for the two pore sizes is selected.

Benefits of technology

The capacitance performance and charging speed of the supercapacitor have been achieved. The specific capacitance value of the pure Ni3 (HITP) 2 electrode film supercapacitor has been increased by 13.2%, and the charging speed has been increased by the largest, 2.4 times that of the pure Ni3 (HITP) 2 electrode film supercapacitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601385A_ABST
    Figure CN119601385A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of electrochemical energy storage, and discloses a supercapacitor based on a mixed MOFs electrode film and a preparation method of the supercapacitor. The preparation method comprises the following steps that two MOFs materials of Ni3 (HITP) 2 and Cu2 (OHPTP) are mixed, a mixed MOFs electrode film is prepared under the action of a binding agent, and the pore size of Ni3 (HITP) 2 is different from that of Cu2 (OHPTP); an ionic liquid matched with Ni3 (HITP) 2 and Cu2 (OHPTP) in size is adopted as an electrolyte; and packaging the mixed MOFs electrode film and an electrolyte to obtain the supercapacitor. According to the invention, two MOFs materials of Ni3 (HITP) 2 and Cu2 (OHPTP) with different apertures are mixed and are matched with the ionic liquid electrolyte, so that the prepared MOFs-based supercapacitor can realize comprehensive improvement of capacitive performance and charging speed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field related to electrochemical energy storage, and more specifically, relates to a supercapacitor based on a mixed MOFs electrode film and a preparation method thereof. Background Art

[0002] Metal-Organic Frameworks (MOFs) refer to a class of crystalline materials that are interconnected by coordination bonds between metal ions or metal ion clusters and organic ligands to form a spatially ordered arrangement. Due to its many advantages such as high porosity, adjustable structure, large specific surface area, and functional doping, MOFs have received extensive research attention and practical applications in many fields such as gas adsorption or separation, catalytic reactions, biomedical applications, and chemical sensing. With the continuous and in-depth exploration of the conductive mechanism of MOFs materials, a series of conductive MOFs with high conductivity have been successfully prepared, which makes this type of material show great development potential and broad application prospects in the field of electrochemical energy storage.

[0003] In recent years, due to the rise of conductive MOFs formed by the coordination of multi-organic ligands and transition metal ions, supercapacitors based on conductive MOFs have gradually attracted the attention of researchers. Studies have shown that in the micro-nanopore region (less than 2nm), the capacitance performance and charging speed of the electrode show a damped oscillation trend with the pore size. However, the conductive MOFs supercapacitors reported so far all have problems such as low capacitor capacitance performance and slow charging speed.

[0004] Therefore, there is an urgent need to solve the technical problems of insufficient capacitance performance and charging speed of conductive MOFs-based supercapacitors. Summary of the invention

[0005] In view of the above defects or improvement needs of the prior art, the present invention provides a supercapacitor based on a hybrid MOFs electrode membrane and a preparation method thereof. The supercapacitor is prepared by mixing two MOFs materials with different pore sizes, Ni3(HITP)2 and Cu2(OHPTP), with a multi-porous electrode membrane composed of a binder, and selecting an ionic liquid electrolyte that is compatible with the two pore sizes, thereby solving the technical problems of insufficient capacitance performance and charging speed of conductive MOFs-based supercapacitors.

[0006] To achieve the above-mentioned purpose, according to one aspect of the present invention, a method for preparing a supercapacitor based on a hybrid MOFs electrode film is provided, comprising the following steps: mixing two MOFs materials, Ni3(HITP)2 and Cu2(OHPTP), and preparing a hybrid MOFs electrode film under the action of a binder, wherein the pore sizes of the Ni3(HITP)2 and the Cu2(OHPTP) are different; using an ionic liquid that matches the size of the Ni3(HITP)2 and the Cu2(OHPTP) as an electrolyte; and encapsulating the hybrid MOFs electrode film and the electrolyte to obtain a supercapacitor.

[0007] Preferably, the ratio of the pore size of the Ni3(HITP)2 to the size of the ions or ion clusters in the electrolyte is 1:2, 3:2 or 5:2, and the ratio of the pore size of the Cu2(OHPTP) to the size of the ions or ion clusters in the electrolyte is 1:2, 3:2 or 5:2.

[0008] Preferably, the mass ratio of the Ni3(HITP)2 and the Cu2(OHPTP) is 1:4 to 4:1.

[0009] Preferably, two MOFs materials, Ni3(HITP)2 and Cu2(OHPTP), are mixed, evenly mixed into agglomerates under the action of a binder, and rolled to obtain a mixed MOFs electrode film; wherein the thickness of the mixed MOFs electrode film is 100 to 200 μm.

[0010] Preferably, the electrolyte is one or more of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and tetramethylammonium tetrafluoroborate.

[0011] Preferably, the electrolyte is preferably an electrolyte formed by mixing 1-ethyl-3-methylimidazolium tetrafluoroborate and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide.

[0012] Preferably, the binder is polytetrafluoroethylene or polyvinylidene fluoride.

[0013] Preferably, the process of preparing the hybrid MOFs electrode membrane further comprises: adjusting the bonding state by adding a diluent after adding the binder;

[0014] Wherein, when the binder is polytetrafluoroethylene, the diluent is anhydrous ethanol; when the binder is polyvinylidene fluoride, the diluent is N-methylpyrrolidone.

[0015] Preferably, the hybrid MOFs electrode membrane and the electrolyte are packaged to obtain a supercapacitor, specifically comprising: placing a diaphragm between two hybrid MOFs electrode membranes, filling the electrolyte, and packaging to obtain a supercapacitor.

[0016] According to another aspect of the present invention, a supercapacitor prepared according to the method for preparing a supercapacitor based on a hybrid MOFs electrode film provided in one aspect of the present invention is provided.

[0017] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0018] The present invention mixes two MOFs materials with different pore sizes, Ni3(HITP)2 and Cu2(OHPTP), and matches them with ionic liquid electrolytes, so that the prepared MOFs-based supercapacitor can achieve comprehensive improvement in capacitance performance and charging speed. This is because the pore size of the conductive MOF determines its pore structure, which in turn affects its capacitance performance, and only a single pore size makes it difficult to match the ion size of the mixed ionic liquid electrolyte, resulting in limited charging speed. The present invention mixes two MOFs materials with different pore sizes, Ni3(HITP)2 and Cu2(OHPTP), and prepares a mixed MOFs electrode membrane under the action of a binder, which can match the ionic liquid electrolyte to the maximum extent; and the ions or ion clusters in the selected ionic liquid electrolyte are matched with the two different pore sizes of Ni3(HITP)2 and Cu2(OHPTP), so that the MOFs-based supercapacitor of the present invention achieves a comprehensive improvement in capacitance performance and charging speed performance.

[0019] Preferably, when the mixed mass ratio of Ni3(HITP)2 and Cu2(OHPTP) in the mixed electrode film is 1:4 to 4:1, it can be adapted to the ionic liquid electrolyte currently used in supercapacitors, such as one or more of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and tetramethylammonium tetrafluoroborate (TMABF4). The above two MOFs, in which Ni3(HITP)2 has a larger pore size of 1.54nm and Cu2(OHPTP) has a smaller pore size of 1.1nm, both satisfy the relationship of half-integer multiples of the size of ions or ion clusters in the ionic electrolyte, so that the ionic liquid electrolyte currently used in supercapacitors can enter the corresponding MOFs pores in a more orderly manner, thereby producing a higher specific capacitance value and significantly improving the charging speed.

[0020] Preferably, when the mass ratio of Ni3(HITP)2 and Cu2(OHPTP) in the mixed MOFs electrode film is 1:4 to 4:1, and the electrolyte is 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4) or 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIMTFSI) and a mixture thereof, the supercapacitor of the mixed MOFs electrode film in the present invention has the largest improvement in charging speed compared with the supercapacitor of the single electrode film under the mixed ionic liquid electrolyte system with a volume ratio of 2:3, which is 2.4 times that of the pure Ni3(HITP)2 electrode film supercapacitor; at the same time, under this electrolyte system, the capacitance performance is improved the most, and the specific capacitance value of the pure Ni3(HITP)2 electrode film supercapacitor is increased by 13.2%. This is due to the larger ion size of TFSI - They tend to enter the pores of Cu2(OHPTP) with a pore size of 1.1nm, causing them to accumulate more densely in the pores, while larger anion clusters tend to enter the pores of Ni3(HITP)2 with a pore size of 1.54nm, resulting in a higher specific capacitance value. At the same time, since single ions and ion clusters can enter two different pores in an orderly manner respectively, the time for ion transmission in the pores is effectively reduced, significantly improving the charging speed.

[0021] Preferably, the process of preparing the mixed MOFs electrode membrane also includes: adjusting the oscillation and ultrasonic time, and after adding the binder, adjusting the bonding state by adding a diluent so that the MOFs material is evenly mixed and distributed in the binder, thereby improving the uniformity of the supercapacitor pore structure. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 The adsorption curve of Ni3(HITP)2 and its pore size distribution diagram according to the example of the present invention, wherein the inset is the pore size distribution diagram.

[0023] Figure 2 It is the adsorption curve of Cu2(OHPTP) and its pore size distribution diagram of the example of the present invention, wherein the inset is the pore size distribution diagram.

[0024] Figure 3 These are structural diagrams of two MOFs materials used as examples in the present invention. The left diagram is the structural diagram of Ni3(HITP)2, and the right diagram is the structural diagram of Cu2(OHPTP).

[0025] Figure 4 This is a scanning electron microscope image of a mixed electrode film prepared from Ni3(HITP)2 and Cu2(OHPTP) in a mass ratio of 4:1 and its element distribution test diagram, wherein the inset is the element distribution test diagram.

[0026] Figure 5A supercapacitor prototype is obtained by encapsulating a mixed electrode film of Ni3(HITP)2 and Cu2(OHPTP) in a mass ratio of 1:4 in Example 1 of the present invention, and a mixed electrolyte of EMIMBF4 and EMIMTFSI in a volume ratio of 2:3, and a photo of the LED lamp lit after charging, wherein the inset is a photo of the LED lamp lit after charging.

[0027] Figure 6 The capacitive performance of the supercapacitor with mixed MOFs electrode membrane and the supercapacitor with single electrode membrane exemplified in the present invention.

[0028] Figure 7 The charging time of the supercapacitor with mixed MOFs electrode membrane and the supercapacitor with single electrode membrane according to the example of the present invention.

[0029] Figure 8 This is a scanning electron microscope image of the mixed electrode film prepared by Ni3(HITP)2 and Cu2(OHPTP) in a mass ratio of 2:3 in the present invention and its element distribution test diagram, wherein the inset is the element distribution test diagram.

[0030] Fig. 9 This is a scanning electron microscope image of a mixed electrode film prepared from Ni3(HITP)2 and Cu2(OHPTP) in a mass ratio of 1:4 and its element distribution test diagram, wherein the inset is the element distribution test diagram. DETAILED DESCRIPTION

[0031] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0032] The HITP in the Ni3(HITP)2 of the present invention is 2,3,6,7,10,11-hexamidintriphenylene. The preparation method of Ni3(HITP)2 is as follows:

[0033] (1) Add 120 mL of 2.33 mmol / L nickel acetate solution (the solvent is a mixture of DMA and DMF, volume ratio 1:1) into a 500 mL beaker and preheat it to 65 °C;

[0034] (2) adding 80 mL of 2 mol / L sodium acetate aqueous solution into the beaker containing the nickel acetate solution in step (1), and continuing to heat to 65° C.;

[0035] (3) Add 30 mL of 2,3,6,7,10,11-hexaaminotriphenylene hydrochloride (HATP·6HCl) aqueous solution to the beaker of the mixed solution in step (2), and react the mixed solution at 65° C. for 4 h;

[0036] (4) After the reaction is completed and the solution is cooled to room temperature, the supernatant is removed and the remaining precipitate is centrifuged and filtered to obtain Ni3(HITP)2;

[0037] (5) The solid was then washed with deionized water and methanol for three times respectively. The single washing process was as follows: the solid was transferred into a beaker, 180 mL of the washing solvent was added thereto, and after stirring at room temperature for 40 min, the filter cake was obtained by vacuum filtration;

[0038] (6) The filter cake was placed in a vacuum drying oven and dried at room temperature for 24 h to obtain the clean final product Ni3(HITP)2.

[0039] like Figure 1 As shown, the adsorption diagram of Ni3(HITP)2 material shows that it exhibits obvious micropore adsorption characteristics, and the pore size distribution curve shows that it has a single pore with a pore size of 1.54 nm.

[0040] The OHPTP in the Cu2(OHPTP) of the present invention is 2,3,6,7,11,12,15,16-octahydroxyphenanthro[9,10:b]triphenylene. The preparation method of Cu2(OHPTP) is as follows:

[0041] (1) Add 12 mg of OHPTP powder, 9.6 mg of copper acetate monohydrate, and 2.3 mL of deionized water into a 10 mL reactor;

[0042] (2) subjecting the above solution to ultrasonic treatment for 10 min until the suspension is uniformly mixed;

[0043] (3) Add 1 mL of DMF (N,N-dimethylformamide) to the reactor and continue ultrasonic treatment for 5 min;

[0044] (4) After sealing the reactor, place it in an oven preheated to 85°C and react for 12 to 16 hours;

[0045] (5) After the reaction is completed, the reactor is cooled to room temperature, and the reaction solution is centrifuged and filtered, and then washed twice with 100 mL of deionized water and 20 mL of acetone, respectively, and the washing is carried out by vacuum filtration;

[0046] (6) The filter cake was placed in a vacuum drying oven and dried at room temperature for 24 h to obtain the clean final product Cu2(OHPTP).

[0047] like Figure 2As shown, the adsorption diagram of Cu2(OHPTP) material shows that it exhibits obvious micropore adsorption characteristics, and the pore size distribution curve shows that it has a single pore with a pore size of 1.1 nm.

[0048] According to the present invention, the raw materials used in the hybrid MOFs electrode membrane provided are Ni3(HITP)2 and Cu2(OHPTP), the conductive MOF with a larger pore size uses Ni3(HITP)2 (pore size of 1.54nm), and the conductive MOF with a smaller pore size uses Cu2(OHPTP) (pore size of 1.10nm). The structural diagrams of the two MOFs are shown in Figure 3 shown.

[0049] A method for preparing a supercapacitor based on a hybrid MOFs electrode film is provided below. The specific steps of the preparation are as follows:

[0050] (1) Weigh 10-40 mg of Ni3(HITP)2 powder and 10-40 mg of Cu2(OHPTP) powder into a 5 mL beaker;

[0051] (2) placing the beaker on a turbine oscillator to oscillate the two powders to mix evenly;

[0052] (3) Add a diluent to the beaker and ultrasonicate the mixture, then add a binder compatible with the diluent. In the present invention, the binder is 6.2 μL of 60% (mass fraction) polytetrafluoroethylene concentrate, with 0.5 to 2 mL of anhydrous ethanol as the diluent, which is dispersed between the MOF particles to connect the particles and form a film; polyvinylidene fluoride can also be used as a binder and N-methylpyrrolidone as its diluent;

[0053] (4) physically stirring the mixture in the beaker until it forms a clumping mass;

[0054] (5) placing the mass on a double-roller mill for rolling, and repeating this step 2 to 3 times to form a mixed MOFs electrode membrane with a thickness of 100 to 200 μm;

[0055] (6) placing the mixed MOFs electrode membrane in a vacuum drying oven and drying until the liquid is completely volatilized, thereby obtaining a mixed MOFs electrode membrane with multiple pore sizes;

[0056] (7) preparing an electrolyte; the electrolyte described in the present invention is tetramethylammonium tetrafluoroborate (TMABF4), 1-ethyl-3-methylimidazolium tetrafluoroborate (EMIMBF4) or 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMIMTFSI), preferably EMIMBF4 and EMIMTFSI are mixed in any volume fraction to prepare an ionic liquid mixture electrolyte, or one of EMIMBF4 and EMIMTFSI is used as a single electrolyte;

[0057] (8) Using a puncher, the electrode film is cut into 10 mm discs and the Celgard 3501 separator is cut into 18 mm discs; the separator is placed between two hybrid MOFs electrode films, filled with the above-mentioned electrolyte, and packaged to obtain a supercapacitor based on the hybrid MOFs electrode film.

[0058] The following are specific embodiments:

[0059] Embodiment 1:

[0060] (1) Weigh 40 mg of Ni3(HITP)2 powder and 10 mg of Cu2(OHPTP) powder into a 5 mL beaker;

[0061] (2) Place the beaker on a turbine oscillator and oscillate for 10 min to mix the two powders evenly;

[0062] (3) 2 mL of ethanol was added to the beaker and the mixture was sonicated for 10 min, followed by the addition of 6.2 μL of 60% polytetrafluoroethylene concentrate;

[0063] (4) physically stirring the mixture in the beaker until it forms a clumping mass;

[0064] (5) placing the mass on a double-roller mill and rolling the mass 2 to 3 times to form a mixed MOFs electrode membrane with a thickness of 150 μm;

[0065] (6) placing the mixed MOFs electrode membrane in a vacuum drying oven and drying it for 24 hours to obtain a porous mixed MOFs electrode membrane;

[0066] (7) EMIMBF4 and EMIMTFSI were mixed in volume ratios of 4:1, 3:2, 2:3, and 1:4 to prepare ionic liquid mixture electrolytes, and EMIMBF4 and EMIMTFSI were used as single ionic liquids as electrolytes for a total of 6 experiments with the above electrode film preparation;

[0067] (8) Using a puncher, the electrode film is cut into 10 mm discs and the Celgard 3501 separator is cut into 18 mm discs; the separator is placed between two hybrid MOFs electrode films, filled with the above-mentioned electrolyte, and packaged to obtain a supercapacitor based on the hybrid MOFs electrode film.

[0068] Comparative Example 1:

[0069] The difference from Example 1 is that the electrode material selected is 50 mg of Ni3(HITP)2 powder.

[0070] Comparative Example 2:

[0071] The difference from Example 1 is that the electrode material selected is 50 mg of Cu2(OHPTP) powder.

[0072] Figure 4 The scanning electron microscope image and element distribution of the electrode film prepared by mixing Ni3(HITP)2 and Cu2(OHPTP) in a mass ratio of 4:1 in Example 1 show that its particle distribution is very uniform.

[0073] Figure 5 This is a picture of a supercapacitor prototype prepared by the method of Example 1 and a photo of the LED lamp successfully lit after charging; wherein Ni3(HITP)2 and Cu2(OHPTP) are mixed in a mass ratio of 4:1 to prepare a mixed MOFs electrode film, and EMIMBF4 and EMIMTFSI are mixed in a volume fraction ratio of 2:3 to prepare a mixed electrolyte.

[0074] Figure 6 and Figure 7 The performance of supercapacitors prepared by mixing the porous mixed MOFs electrode membrane prepared by mixing Ni3(HITP)2 and Cu2(OHPTP) in a mass ratio of 4:1 in Example 1 and encapsulating them with 6 groups of different electrolytes, as well as the performance of supercapacitors prepared by encapsulating Ni3(HITP)2 as a single pore size electrode membrane with 6 groups of different electrolytes in Comparative Example 1.

[0075] from Figure 6 and Figure 7It can be seen that the volume fractions of 0% and 100% correspond to single ionic liquids EMIMBF4 and EMIMTFSI, respectively. For the mixed MOFs electrode membrane prepared by mixing Ni3(HITP)2 and Cu2(OHPTP) at a mass ratio of 4:1, the supercapacitor of the mixed MOFs electrode membrane has the most improved capacitance performance compared with the supercapacitor of the single electrode membrane in the mixed ionic liquid electrolyte system with a volume ratio of 2:3, and the specific capacitance value of the supercapacitor of the pure Ni3(HITP)2 single electrode membrane has increased by 13.2%; at the same time, the charging speed is improved the most in this system, which is 2.4 times that of the pure Ni3(HITP)2 electrode membrane supercapacitor.

[0076] Embodiment 2:

[0077] (1) Weigh 20 mg of Ni3(HITP)2 powder and 30 mg of Cu2(OHPTP) powder into a 5 mL beaker;

[0078] (2) Place the beaker on a turbine oscillator and oscillate for 8 minutes to mix the two powders evenly;

[0079] (3) 1 mL of ethanol was added to the beaker and the mixture was sonicated for 8 min, followed by the addition of 6.2 μL of 60% polytetrafluoroethylene concentrate;

[0080] (4) physically stirring the mixture in the beaker until it forms a clumping mass;

[0081] (5) placing the mass on a double-roll mill and rolling it to form a mixed MOFs electrode membrane with a thickness of 150 μm, and repeating this step twice;

[0082] (6) placing the mixed MOFs electrode membrane in a vacuum drying oven and drying it for 24 hours to obtain a porous mixed MOFs electrode membrane;

[0083] (7) mixing 40% by volume of the ionic liquid EMIMBF4 and 60% by volume of the EMIMTFSI to prepare an ionic liquid mixture electrolyte;

[0084] (8) Using a puncher, the electrode film is cut into 10 mm discs and the Celgard 3501 separator is cut into 18 mm discs; the separator is placed between two hybrid MOFs electrode films, filled with the above-mentioned electrolyte, and packaged to obtain a supercapacitor based on the hybrid MOFs electrode film.

[0085] Figure 8 Shown is the scanning electron microscope image and element distribution of the electrode film prepared by Ni3(HITP)2 and Cu2(OHPTP) in a mass ratio of 2:3 in Example 2. It can be seen that the particle distribution of the mixed MOFs electrode film is very uniform.

[0086] Embodiment 3:

[0087] (1) Weigh 10 mg of Ni3(HITP)2 powder and 40 mg of Cu2(OHPTP) powder into a 5 mL beaker;

[0088] (2) Place the beaker on a turbine oscillator and oscillate for 6 minutes to mix the two powders evenly;

[0089] (3) 0.5 mL of ethanol was added to the beaker and the mixture was sonicated for 6 min, followed by the addition of 6.2 μL of 60% polytetrafluoroethylene concentrate;

[0090] (4) physically stirring the mixture in the beaker until it forms a clumping mass;

[0091] (5) placing the mass on a double-roll mill and rolling it to form a mixed MOFs electrode membrane with a thickness of 150 μm, and repeating this step three times;

[0092] (6) placing the mixed MOFs electrode membrane in a vacuum drying oven and drying it for 24 hours to obtain a mixed MOFs electrode membrane with multiple pore sizes;

[0093] (7) mixing 20% ​​by volume of ionic liquid EMIMBF4 and 80% by volume of EMIMTFSI to prepare an ionic liquid mixture electrolyte;

[0094] (8) Using a puncher, the electrode film is cut into 10 mm discs and the Celgard 3501 separator is cut into 18 mm discs; the separator is placed between two hybrid MOFs electrode films, filled with the above-mentioned electrolyte, and packaged to obtain a supercapacitor based on the hybrid MOFs electrode film.

[0095] Fig. 9 Shown is a scanning electron microscope image of the electrode film prepared with Ni3(HITP)2 and Cu2(OHPTP) in a mass ratio of 1:4 in Example 3 and its element distribution. It can be seen that the particle distribution of the mixed MOFs electrode film is very uniform.

[0096] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the present invention and its equivalent technologies, the present invention is also intended to include these modifications and variations. The above-described embodiments are only preferred embodiments for fully illustrating the present invention, and their protection scope is not limited thereto. Equivalent substitutions or changes made by those skilled in the art based on the present invention are all within the protection scope of the present invention.

Claims

1. A method for preparing a supercapacitor based on a hybrid MOFs electrode film, characterized in that: The steps include: Two MOFs materials, Ni3(HITP)2 and Cu2(OHPTP), are mixed to obtain a mixed MOFs electrode membrane under the action of a binder, wherein the pore sizes of the Ni3(HITP)2 and the Cu2(OHPTP) are different; an ionic liquid that matches the sizes of the Ni3(HITP)2 and the Cu2(OHPTP) is used as an electrolyte; and the mixed MOFs electrode membrane and the electrolyte are packaged to obtain a supercapacitor.

2. The method for preparing a supercapacitor based on a hybrid MOFs electrode film according to claim 1, characterized in that: The ratio of the pore size of the Ni3(HITP)2 to the size of the ions or ion clusters in the electrolyte is 1:2, 3:2 or 5:2, and the ratio of the pore size of the Cu2(OHPTP) to the size of the ions or ion clusters in the electrolyte is 1:2, 3:2 or 5:

2.

3. The method for preparing a supercapacitor based on a hybrid MOFs electrode film according to claim 1, characterized in that: The mass ratio of the Ni3(HITP)2 and the Cu2(OHPTP) is 1:4 to 4:

1.

4. The method for preparing a supercapacitor based on a hybrid MOFs electrode film according to claim 1, characterized in that: In the preparation process of the hybrid MOFs electrode film: Two MOFs materials, Ni3(HITP)2 and Cu2(OHPTP), are mixed, mixed evenly into agglomerates under the action of a binder, and rolled to obtain a mixed MOFs electrode film; wherein the thickness of the mixed MOFs electrode film is 100 to 200 μm.

5. The method for preparing a supercapacitor based on a hybrid MOFs electrode film according to claim 1, characterized in that: The electrolyte is one or more of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and tetramethylammonium tetrafluoroborate.

6. The method for preparing a supercapacitor based on a hybrid MOFs electrode film according to claim 5, characterized in that: The electrolyte is preferably an electrolyte formed by mixing 1-ethyl-3-methylimidazolium tetrafluoroborate and 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide.

7. The method for preparing a supercapacitor based on a hybrid MOFs electrode film according to claim 1, characterized in that: The binder is polytetrafluoroethylene or polyvinylidene fluoride.

8. The method for preparing a supercapacitor based on a hybrid MOFs electrode film according to claim 7, characterized in that: The process of preparing the hybrid MOFs electrode film also includes: after adding the binder, adjusting the bonding state by adding a diluent; Wherein, when the binder is polytetrafluoroethylene, the diluent is anhydrous ethanol; when the binder is polyvinylidene fluoride, the diluent is N-methylpyrrolidone.

9. The method for preparing a supercapacitor based on a hybrid MOFs electrode film according to claim 1, characterized in that: The mixed MOFs electrode film and the electrolyte are packaged to obtain a supercapacitor, specifically comprising: The separator is placed between two mixed MOFs electrode films, filled with the electrolyte, and packaged to obtain a supercapacitor.

10. A supercapacitor prepared according to the method for preparing a supercapacitor based on a hybrid MOFs electrode film according to claims 1-9.

Citation Information

Patent Citations

  • A ternary composite material and a preparation method and application thereof

    CN109036862A

  • Low-viscosity III-type porous liquid and preparation method thereof

    CN112138506A

  • MOFs ionic liquid supercapacitor and production method thereof

    CN113593933A

  • Method and device for manufacturing electrode of ionic liquid-based supercapacitor and method for manufacturing such supercapacitor

    CN114207757A

  • Preparation method and application of double-electric-layer supercapacitor electrode material

    CN118571666A